MEKANISME GANTI RUGI TERHADAP KORBAN KECELAKAAN LALU LINTAS MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Budimah Budimah (Maleo Law Journal, 2017)
According to the development of the era and the increase of the population, the human need for transportation will also increase from day to day rapidly, so that public roads that are already available are becoming more crowded. It carries a very high risk for motorists and other public road users. In its development, the perpetrators of road traffic accidents are many who give compensation to the victim as a form of accountability. This is in accordance with the principle of absolute responsibility in which the perpetrator is accountable to the victim because of the result of the negligence committed by the offender causing harm to the victim. However, compensation to victims of traffic accidents provided by perpetrators does not abolish corporal punishment (imprisonment or confinement). Because for the victims who have died, life can not be replaced by anything even with money worth trillions of rupiahKeywords: compensation, Victim, Traffic accident